2019
DOI: 10.1029/2019jb017803
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Changes of Seismic Properties in the Entire Crust Beneath Japan After the Mw 9.0, 2011 Tohoku‐oki Earthquake

Abstract: Studies of mechanical responses of the Earth crust to large earthquakes can provide us with unique insights into the processes of stress buildup and release. As a complement to geodetic methods that derive crustal strain dynamics from surface observations (e.g., GPS, InSAR), noise‐based seismic velocity monitoring directly probes the mechanical state of the crust, at depth and continuously in time. We investigate the responses of the crust to the Mw 9.0, 2011 Tohoku‐oki earthquake. In addition to the Hi‐net sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…This latter value agrees with other estimates based on tidal-dv/v responses (Takano et al, 2014;Yamamura et al, 2003). Our estimations are also in agreement with dilatant induced velocity reduction during slow slip in the lower crust (Rivet et al, 2011;Wang et al, 2019).…”
Section: Journal Of Geophysical Research: Solid Earthsupporting
confidence: 93%
See 1 more Smart Citation
“…This latter value agrees with other estimates based on tidal-dv/v responses (Takano et al, 2014;Yamamura et al, 2003). Our estimations are also in agreement with dilatant induced velocity reduction during slow slip in the lower crust (Rivet et al, 2011;Wang et al, 2019).…”
Section: Journal Of Geophysical Research: Solid Earthsupporting
confidence: 93%
“…The energy velocity is determined by the equipartition state. We take the theoretical equipartition ratio as 10.4 and 3 for a Poisson solid (Margerin et al, 2000;Weaver, 1982), the same as Wang et al (2019), for further calculation. We solved for the body wave depth sensitivity normalized to 30 km depth with each layer 1 km thick layer.…”
Section: Window Numbermentioning
confidence: 99%
“…Studies of the mechanical responses of the earth’s crust to large earthquakes can provide us with unique insights into the processes of stress buildup and release at depth (Bürgmann and Dresen, 2008). At this stage, we mainly observe a rapid coseismic velocity reduction followed by a slow postseismic exponential recovery process (Field et al, 1998; Wegler and Sens‐Schönfelder, 2007; Brenguier et al, 2008a, Xu ZJ and Song XD, 2009; Sawazaki et al, 2009; Chen JH et al, 2010; Cheng X et al, 2010; Zhao PP et al, 2012; Froment et al, 2013; Acarel et al, 2014; Brenguier et al, 2014; Liu ZK et al, 2014; Hong TK et al, 2017; Liu ZK et al, 2018; Wang QY et al, 2019; Poli et al, 2020). The predominant mechanism underlying the observed earthquake‐related velocity drop is referred to as shallow dynamic shaking (Sleep, 2015) and deep stress changes by the earthquake.…”
Section: Application and Observation Of Ambient Seismic Noise‐based Mmentioning
confidence: 84%
“…Here we present a recent study by Wang QY et al (2019) related to the 2011 M w 9.0 Tohoku‐Oki earthquake off the coast of Japan. The authors identified depth (frequency)‐dependent seismic velocity changes.…”
Section: Application and Observation Of Ambient Seismic Noise‐based Mmentioning
confidence: 99%
See 1 more Smart Citation